2022
DOI: 10.1108/maj-07-2021-3232
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management and investor protection during the COVID-19 pandemic: evidence from G-12 countries

Abstract: Purpose The purpose of this paper is to examine the inter-relations among the strength of investor protection institutions, earnings management (EM) and the COVID-19 pandemic. Design/methodology/approach As a proxy for EM, the authors use discretionary accruals measure, estimated using the modified Jones model (1991). As a proxy for the strength of investor protection institutions, the study uses the Investor Protection Index, extracted from the Global Competitiveness Reports. The sample consists of 5,519 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 67 publications
3
34
0
5
Order By: Relevance
“…Both AEM and REM mean values decrease during the pandemic and the One sample T-test results confirm that both figures are significantly different from one another. The decreases in both proxies of EM indicate that firms participate in fewer earnings management activities during the pandemic period, which is consistent with earlier studies, such as Ali et al (2022) and Azizah (2021), who found that firms restrict their earnings manipulation during difficult times.…”
Section: Results and Discussion Descriptive Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Both AEM and REM mean values decrease during the pandemic and the One sample T-test results confirm that both figures are significantly different from one another. The decreases in both proxies of EM indicate that firms participate in fewer earnings management activities during the pandemic period, which is consistent with earlier studies, such as Ali et al (2022) and Azizah (2021), who found that firms restrict their earnings manipulation during difficult times.…”
Section: Results and Discussion Descriptive Analysissupporting
confidence: 90%
“…The financial difficulties during the pandemic have a long-term negative effect on the reliability of financial statements thus, encouraging managers to engage in accrual earnings management to enhance the presentation of their financial reality to their investors. On the contrary, Ali et al (2022) recently reported in their study that the overall amount of discretionary accruals reported in the financial statements of listed firms in G-12 countries decreased during the pandemic, suggesting that the economic effects of the pandemic may be comparable to those of the financial crisis in 2008.…”
Section: Financial Distress and Accrual Earnings Management (Aem)mentioning
confidence: 77%
“…Immediate policy responses at both the federal and state levels (border closures, social distancing and lockdowns) to the COVID-19 outbreak have resulted in unprecedented disruptions to daily life and economic activities across Australia. In the wake of this pandemic-induced carnage, there have been extensive debates around the need to reduce corporate exposure to existential risks, especially to those relating to sustainable development (Bapuji et al , 2020; Brammer et al , 2020; Ali et al , 2022). When changing their business strategies, Australian firms are particularly concerned if current sustainability practices should be part of the “new” business post-COVID-19 due to the additional short-term costs associated with sustainable business practices.…”
Section: Introductionmentioning
confidence: 99%
“…The paper “ Earnings management and investor protection during the COVID-19 pandemic: evidence from G-12 countries ” by Ali et al (2022) aimed to determine the interrelations among the strength of investor protection institutions and earnings management (EM) during the COVID-19 pandemic. Their sample included 5,519 firms listed in the G-12 countries during 2015–2020.…”
Section: Contents Of the Special Issuementioning
confidence: 99%